Analysis of the Impact of Organizational Learning and Inter-Firm Resources on Firm Performance with Innovation, Dynamic Resilience, and Managed Service Quality (Msq) as Intervening Variables at PT. Telkom Akses - Supriyanto, Aji; Noviaristanti, Siska (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes the effect of Organizational Learning and Inter-firm Resources on Firm Performance, with Innovation, Dynamic Resilience, and Managed Service Quality (MSQ) as intervening variables at PT Telkom Akses. Using quantitative methods with the SEM-PLS approach and SmartPLS tools, data was obtained from 61 General Managers and Managers. The results show Organizational Learning has no significant effect on Firm Performance (T-Value 0.950; P-Value 0.342), while Inter-firm Resources has a significant effect (T-Value 2.234; P-Value 0.026). These findings emphasize the importance of external collaboration and service quality management in improving firm performance.